Word Heritage Sites as soft tourism destinations – their impacts on international arrivals and tourism receipts - Bacsi, Zsuzsanna; Tóth, Éva (Bulletin of Geography. Socio-economic Series, 2019)
The paper deals with the relationship between the presence of world heritage sites in a country and the volume of international tourist arrivals and international tourism receipts. World heritage sites are unique tourist attractions with enhanced attention paid to their protection, preservation and sustainability. The paper analyses whether the needs of sustainability can be harmonised with the requirements of a profitable and successful tourism sector, by statistical analysis of data about world heritage sites and tourism performance, for 129 countries of the world from 2014 to 2017. The results show that both cultural and natural world heritage sites are generally strong attractions for tourists and can contribute to increased arrivals and receipts. Cultural sites were found to have higher impact on arrivals, while natural heritage sites seemed to have more impact on receipts, which suggest, that visitors of natural world heritage sites are usually higher spenders, than tourists visiting cultural sites. Countries widely differ, however, in this respect by their geographical locations. Countries in Europe and Latin-America & the Caribbean region benefit most from cultural world heritage sites, while African, and North American countries experienced the benefits of natural world heritage sites more. The general level of development measured by per capita GNI also mattered for the less developed areas, but not so much for developed regions that possess a suitable level of infrastructure, health and education, and living standards.